Analisis Rencana Pelaksanaan Pembelajaran Kelas X Mapel PJOK Ditinjau dari HOTS di SMK Se-Kecamatan Kebumen - Nahar Salamah; Hermawan Pamot Raharjo (Universitas Negeri Semarang, 2023)
This study aims to analyze how well the class X PJOK RPP is about learning based on Higher Order Thinking Skills in SMKs in Kebumen District. This research is quantitative descriptive. The method in this research is survey. The population in this study were all PE teachers in SMK throughout Kebumen District The data analysis technique of this research is descriptive analysis. The results of the analysis of the lesson plan analysis for Class X Mapel PE in Vocational Schools throughout the Kebumen District in terms of HOTS showed the